2019
DOI: 10.1002/pits.22295
|View full text |Cite
|
Sign up to set email alerts
|

Teacher power and children's loneliness: Moderating effects of teacher‐child relationships and peer relationships

Abstract: Teacher‐child relationships and peer relationships are important predictors of children's loneliness. However, few studies have examined the potential and adverse relationship between teacher power and children's loneliness. Thus, we explicitly explored whether teacher power is related to children's loneliness and examined the potential moderating roles of interpersonal relationships (i.e., teacher‐child relationships and peer relationships) in 888 Chinese children. Moreover, this study measured teacher power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 117 publications
(168 reference statements)
0
6
1
Order By: Relevance
“…Second, although several previous studies highlighted the importance of teacher–student relationships and peer relationships as protective resources against children negative development (Q. Tang et al, 2013; Zhang et al, 2018), our data do not confirm this assumption. Contrary to previous studies and our hypothesis, the present study revealed that teacher–student relationships exacerbated rather than buffered the negative effect of maternal harsh discipline on children’s anxiety.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, although several previous studies highlighted the importance of teacher–student relationships and peer relationships as protective resources against children negative development (Q. Tang et al, 2013; Zhang et al, 2018), our data do not confirm this assumption. Contrary to previous studies and our hypothesis, the present study revealed that teacher–student relationships exacerbated rather than buffered the negative effect of maternal harsh discipline on children’s anxiety.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that pupils' perceptions of increased teacher power are associated with negative pupil‐teacher relationships and an emotional distance between pupil and teacher (Zhang et al, 2019). Although Zhang et al's study is conducted on Chinese schoolchildren, who experience a very different educational culture than in the UK, their findings support Magee and Smith's (2013) proposition that an increasing power differential in dyadic relationships increases social distance.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant items were averaged, with higher averaged scores indicating a better teacher‐student relationship, as perceived by the students. This measure is considered to be a valid and reliable instrument for measuring students' perceptions of teacher‐student relationships (Lin et al., 2016; Shi et al., 2022; Zhang, Jiang, Lei, & Huang, 2019). Confirmatory factor analysis showed that the 4‐factor structure validity of the scale was good (ꭓ 2 / df = 3.46, RMSEA = 0.05, CFI = 0.94, TLI = 0.93, SRMR = 0.04).…”
Section: Methodsmentioning
confidence: 99%